Vol. 2; Handbook of Measurement in Science and Engineering (2013, 2013)
The Handbook of Engineering Measurements is encyclopedic in scope, beyond anything currently available on the market. The handbook spans several disciplines: Civil and Environmental Engineering, Mechanical and Biomedical Engineering, and Industrial Engine.